Developing of Inquiry-Based Interactive Edpuzzle Media to Improve Students' Mathematics Learning Outcomes - Ernawati Ernawati; Rangga Firdaus; Sugeng Sutiarso; Karwono Karwono (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2023)
Teaching materials and media are one of the important components in a learning process. The lack of teaching materials is one of the impacts of the teacher-centered learning process, so students do not have a culture of independent learning. This study aims to determine the effectiveness of the development of inquiry-based Edpuzzle interactive learning media. This research is a research and development study using a mixed approach (Mixed Method) which aims to determine the effectiveness of edpuzzle product development. By using the ADDIE model, analysis, design, development, implementation and evaluation of the development of a product. The sample of this study amounted to 30 students. The research technique uses an assessment instrument technique. And data analysis using quantitative data from pretest and posttest scores which are then tested using the N-Gain statistical formula. The effectiveness of the development of inquiry-based edpuzzel interactive media products in math number pattern material has a high level of effectiveness with 71.2% results with a very high level of effectiveness, and the Sig. (2-tailed) is 0.000